Sistem Informasi Pemesanan dan Pembayaran Tiket Bus pada PO Bintang Utara Berbasis Web - Sihombing, Ligera; Harianja, Eva Julia G.; Purba, Eviyanti Novita (Universitas Methodist Indonesia, 2024)
Currently, many transactions for ordering and paying for bus tickets are done manually, and it is common for confusion and errors to occur during the process. Therefore, an information system for ordering and paying for bus tickets is needed that is designed to make it easier for the administration to provide and provide better service to prospective passengers. The purpose of developing this system is to create a Bus Ticket Ordering and Payment Information System that is practical and easy to use and can easily provide the data needed. With these reasons, the authors wish to create a system regarding ordering and paying for bus tickets that is built using information technology (web-based).